STUDY PENGARUH PARAMETER PEMOTONGAN TERHADAP GEOMETRI GERAM PADA PEMESINAN LAJU TINGGI, KERAS DAN KERING (DINAMIS, 2014)
In this research, the material of AISI 4140 at 55 HRC was cut using CBN tool in high speed machining, hard and dry machinery process. The chips, as the result of the whole condition of the cutting are observed morphologically and measured geometrically in the case of the thickness. The method used in this research is incremental experiment done in every segment performed in the certain cutting condition. In this case, the varieties of cutting: the speed cutting (V) (m/min), the feed (f) (mm/rev) and the depth of cutting c (mm) are performed. The result shows that the morphology of the chips formed have the geometrical feature such as saw-tooth; the higher the cutting speed (V), the thickness of the chip after the cutting (hc) tends to decrease and the distance between the edges of the saw (δ) tends to increase. Meanwhile the feed parameter (f) and the depth of the cutting (a) is in reverse with the speed of cutting (V) ; the higher the feed (f) and the depth of the cutting (a), the thickness of the chip after cutting (hc) tends to decrease.